INTERNET POLITICS. MAPPING WSIS+10 CONTROVERSIES ON INTERNET GOVERNANCE - Santaniello, Mauro (AoIR Selected Papers of Internet Research, 2016)
The World Summit on Information Society (WSIS) is one of the most important global policy arena for Internet Governance (IG), and IG in turn has soon emerged as the most controversial issue of the Summit. In 2015 the UN has started a review process of the WSIS and of the goals settled in its main policy output: the Tunis Agenda. This process, known as WSIS+10 review, has involved many actors from the classic five stakeholder groups (governments, private sector, civil society, technical and academic community, intergovernmental organisations) mainly through written and standardised submissions to an open call. This paper proposes a comparative analysis of policy preferences expressed on issues relating to Internet governance in the context of the WSIS+10 review process. In the first part of the paper, through a literature review, two main controversies which have emerged around the global governance of the Internet are identified and operationalised: the inclusiveness of decision-making process, and the bindingness of decisions. In the second part of the paper, actors’ preferences are mapped on a bi-dimensional plan crossing the two operationalised variables, based on an hand-coding process of seventy-three documents submitted to the open call. The aim of this paper is to explore stakeholder groups’ specificities, conflict areas and possibilities for coalition. Findings suggest that actors’ preferences are more articulated, dynamic and complex than that depicted in previous literature by means of dichotomies such as globalists versus sovranists, multilateralists versus multistakeholderists, and IGF hawks versus doves.